Popularity of marijuana among Polish students - Michał Pająk; Rafał Mazur; Sebastian Masternak; Katarzyna Skórzyńska-Dziduszko (Kazimierz Wielki University, 2017)
Introduction and the aim: Marijuana is the most commonly used drug in the world (excluding alcohol and tobacco). According to the literature about 16% of Poles at the age of 16 to 64 years old, at least once have used cannabis. The aim of study was to estimate the popularity of marijuana among students of Polish universities. We also asked questions about respondents' attitude towards marijuana and opinions about its validation. Material and methods: The study was conducted in 2017 on 132 individuals - 60 men and 72 women. The results were analyzed in STATISTICA 10 at p<0.05. Results:Out of interviewees, 63.6% of them, at least once in their lives, have used marijuana. This is a percentage of up to four times greater than that one given in the literature for the general population. Even 80% of men and 50% of women have tried marijuana at least once in their lives. Students of Catholic University of Lublin reach for marijuana significantly more often than students of Medical University of Lublin. The majority of respondents (53%) treats marijuana as a "soft" drug, though up 67.4% believe that it has the addictive potential. More than a half of respondents (56.8%) stands for liberalization of rules relevant to marijuana in Poland. Vast majority (70%) of respondents believes that marijuana is easily available in Poland. Conclusions: Marijuana is a drug popular among students. The criminalization of drug use in Poland is not effective for the prevention of its use, the majority of respondents believes that marijuana is easily available in Poland. Considering the negative health and social consequences of the current state, it is worth wondering about making changes in the education system and Polish drug law.